Chemical design and synthesis of superior single-atom electrocatalysts via in situ polymerization. Issue 34 (14th August 2020) - Xu, Haomin; Xi, Shibo; Li, Jing; Liu, Shikai; Lyu, Pin; Yu, Wei; Sun, Tao; Qi, Dong-Chen; He, Qian; Xiao, Hai; Lin, Ming; Wu, Jishan; et al.
Abstract : A novel in situ polymerization approach is developed for the synthesis of well-defined FeN4 -based single-atom catalysts (SACs) on carbon nanotubes with superior catalytic activity in the ORR and Zn–oxygen batteries. Abstract : Molecule-like electrocatalysts with FeN4 motifs have been demonstrated to be excellent candidates for various renewable energy conversions. The ability to further tune the electronic properties of molecular FeN4 motifs and integrate them onto conductive supports represents a key step towards the synthesis of highly robust and efficient single-atom catalysts (SACs) for practical applications. Here, we developed a new route for the synthesis of a well-defined single-atom FeN4 electrocatalyst via in situ polymerization of four amino groups functionalized iron phthalocyanine (NH2 -FePc) molecules on conductive carbon nanotubes. The intermolecular oxidative dimerization between the amino groups of NH2 -FePc creates the desired electron-withdrawing pyrazine linker between FeN4 motifs, which can significantly optimize their electrocatalytic performances. As a result, the FeN4 -SAC exhibits both outstanding ORR activity (a half-wave potential of 0.88 V vs. RHE) and excellent performance in Zn–oxygen batteries, outperforming the commercial Pt/C and pristine iron phthalocyanine (FePc) catalysts. Our theoretical calculations reveal that the presence of electron-withdrawing linkers shifts the occupied antibonding states towards lower energies and thus weakens the Fe–O bond, which is primarily responsible for the enhancement of ORR activity.